The Validity of the Execution Auction of Booty of Motor-vehicle Theft by the State Prosecutors Office - Andreanto Andreanto; Supriyono Supriyono; Anang Dony Irawan (Indonesian Journal of Law and Policy Studies, 2022)
This study aims to determine the role of the state prosecutor's office in the management of evidence and looted goods and to determine the validity of the auction process for the execution of motor vehicle theft stolen goods by the state prosecutor's office. This research is a normative juridical research using a statutory approach. From the results of the study, it can be seen that the execution auction of the booty of motor-vehicle theft carried out by the state prosecutors is considered valid if it meets the prerequisites, namely the existence of a "confiscated" order in a court decision that has been inkracht and fulfills the principle of publicity and fulfills the provisions as stated in the Regulation of the Attorney General of the Republic of Indonesia Number 10 of 2019 concerning Amendments to the Regulation of the Attorney General R.I. No. PER-002/A/JA/05/2017 concerning Auctions and Direct Selling of Confiscated Goods or State confiscated Goods or Executed Confiscated Goods.